FRI0099 Obese patients with rheumatoid arthritis have reduced response rates to biologic anti-rheumatic agents: a comparison between european and american ra patients. (23rd January 2014) - Finckh, A.; Scherer, A.; Kremer, J.; Greenberg, J.; Lubbeke, A.; Schwarz, H.; Rathbun, A.; Gabay, C.; Reed, G.
Abstract : Background: Obesity in RA patients has been associated with an increased risk of comorbidity, total joint replacement, pain, disability, high medical costs and impaired quality of life. One study has suggested that obese patients are less likely to reach remission, but the role of obesity treatment response is not well established. Objectives: To analyze the impact of obesity on RA disease activity in patients initiating their first biologic agent and compare the results from Switzerland and the US. Methods: We included all RA patients from a European (SCQM-RA) and a North-American (CORRONA) RA registry with available Body Mass Index (BMI) who initiate a biologic. Patients were categorized according to the WHO BMI categories as "underweight" (BMI < 18.5), "normal weight" (BMI ≥ 18.5, < 25), "overweight" (BMI ≥ 25, < 30), "obese-I" (BMI ≥ 30, < 35) and "obese-2" (BMI ≥ 35). The primary outcome was the proportion of patients reaching remission or low disease activity (LDA) at 1 year after initiation, based on DAS28 in SCQM, and on CDAI in CORRONA. A secondary outcome was drug retention. Patients who discontinued treatment before 12 months were assumed to be non-responders. Response rates were adjusted for potential confounders using logistic regression. Drug retention was analyzed using a Cox proportional hazard model, adjusting for potential confounders. CORRONA and SCQM were analyzed independently with similar models and results compared. Results: We identified 2707 patients in SCQM and 4633 patients in CORRONA initiating a first biologic with a clinical assessment at initiation and 1-year follow-up. The prevalence of obesity was higher in US than in Swiss patients (41% versus 16%). Remission rates adjusted for drug retention at 1 year were lower in obese patients compared to non-obese patients: In SCQM: 21% in obese versus 33% in normal weight patients. In CORRONA: 9.6% in obese-2, 11.8% in obese-1 versus 16.3% in normal weight patients. The adjusted odds ratio (OR) for remission at 1 year in obese patients were 0.6 (95% CI: 0.43 – 0.84) in SCQM and 0.54 (95% CI: 0.39 – 0.76) for obese-2 patients in CORRONA. The adjusted OR for LDA in obese patients were 0.62 (95% CI: 0.46 – 0.84) in SCQM and 0.8 (95% CI: 0.60 – 1.07) for obese-2 patients CORRONA. A "dose response" existed, with gradually lower likelihoods of remission or LDA in overweight, obese-1, and obese-2 patients. A similar trend existed for drug retention, with progressively higher hazards of discontinuation in overweight and obese patients: The hazard ratio (HR) for drug discontinuation in obese-2 patients was 1.21 (95%CI: 1.07 – 1.36) in CORRONA and 1.06 (0.77 – 1.46) in SCQM. Conclusions: Overall, data from two different populations indicate that obesity is a risk factor for inferior response to biologic agents in patients with longstanding RA. It is uncertain whether this is explained by suboptimal dosing of these therapies in obese patients or by a true biologic effect of adipose tissue. We believe that this is the first report of comparison of obesity and response from a registry in Europe compared with the US. Disclosure of Interest: A. Finckh: None Declared, A. Scherer: None Declared, J. Kremer: None Declared, J. Greenberg Shareholder of: CORRONA, Consultant for: AstraZeneca, CORRONA, Novartis, Pfizer, A. Lubbeke: None Declared, H. Schwarz: None Declared, A. Rathbun: None Declared, C. Gabay: None Declared, G. Reed Employee of: CORRONA